Circadian and seasonal factors in the pathogenesis of acute myocardial infarction: the influence of environmental temperature. Issue 5 (May 1993) - Marchant, B; Ranjadayalan, K; Stevenson, R; Wilkinson, P; Timmis, A D
Abstract : OBJECTIVE–To determine the circadian and seasonal variations in the incidence of acute myocardial infarction and the influence of environmental temperature. PATIENTS–633 consecutive patients with acute myocardial infarction admitted to a coronary care unit over four years. SETTING–Coronary care unit in a district general hospital. DESIGN–An observational study. RESULTS–The onset of acute myocardial infarction had a circadian rhythm with a peak in the second quarter of the day. A seasonal variation was also found with a significant winter peak. There was, however, an excess of infarctions on colder days in both winter and summer indicating that the effect of environmental temperature on the onset of acute myocardial infarction is independent of the time of year. CONCLUSION–Acute myocardial infarction is more common in winter and more common on colder days, independent of season. Environmental temperature may play an important part in the pathogenesis of acute myocardial infarction.